Formulación de una propuesta de mejora en el sistema de planeación de inventarios, basado en un aplicativo excel, para la empresa Avesco S.A.S, en la ciudad de Bogotá (2016)
A suitable control in the stock is what allows them the companies not to generate expenses in products that still are useful in the stores, but that due to the deficient control in the same ones, return to generate the same orders of purchases, obtaining hereby considerable consumptions. It is important to emphasize the necessary and indispensable thing to rely on a model of control that it should allow to generate an alert when one finds a product near becoming exhausted and a control in the inventories that it helps him to the companies to support a daily record of the stock in his stores, to continue with his daily production estimated without falling down in misadventures.